“A perfect storm”: an ethnography of pactice in an adult male prison - O'Mara, Oscar (2024)
Prisons exist in an apparent cycle of crises that fail to achieve their stated aims: security, safety, and rehabilitation. This thesis utilises Bourdieu’s field theory to understand how these macro aims are mediated into practice in Clarendon, a local adult male prison in England, before and during the COVID-19 pandemic. It provides an alternative interpretation of imprisonment and the inter-relations between policy, people, and practises that produce harmful outcomes for prisoners. This ethnographic case study critically analyses how a prison is a paradox of its official aims. The study provides original insights and contributions to extant prison literature on the relationship between social structures, interpersonal attitudes, local practices, and outcomes. It theorises that many prisoners are em-prisoned by a trans-carceral habitus, a disposition informed by shared marginalisation and neglect before, during, and after imprisonment. This is reinforced by an infra-doxic sensibility to the prison, an attachment and an attuned response to its offer of protection from external social deprivation. This disposition and logic are perpetuated by a narrow definition of prison security engendered by staff, where prisoners are conceived as risks to be controlled. These staff are empowered and constrained by the double-game strategy of imprisonment. Policies and training turn decision-making into a theoretical model of rules and responsibilities that structure their practice and provide staff with the symbolic and physical authority to enact control. Their use of force perpetuates the prison as a place of punishment and violence. The pandemic revealed many of these social forces. A novel analysis of the pandemic response indicates an initial disruption, hysteresis, to how imprisonment was experienced with more supportive relationships between prisoners and staff. However, this was a fallacy. This study highlights that Clarendon remained a place of control, hierarchy, and harm, disguised and legitimised by policy. Finally, it speaks to the personal journey of an insider researcher, from a doxosopher (Bourdieu, 1998) to a scholar. Together, this thesis highlights how a prison is a perfect storm, a metaphor for the mutually reinforcing field relations that produce the harmful outcomes of imprisonment. Clarendon is not in a crisis, it is the crisis, a product of its own conditions.